1989
DOI: 10.1007/bf02308093
|View full text |Cite
|
Sign up to set email alerts
|

Levels of indole-3-acetic acid in vigorous and genetic dwarf apple trees

Abstract: Abstract. Seasonal levels of indole-3-acetic acid (IAA) present in buds, meristematic tissues, and leaves of 1-year-old shoots of two selections (vigorous and dwarf) of a F2 generation apple population with original "Goldspur" × "Redspur" parentage were determined using gas chromatography-selected ion monitoring-mass spectrometry (GC-SIM-MS) with a 13C-IAA internal standard. A comparison of IAA levels through one growing season was made in the shoots of two trees differing in growth. The levels of IAA in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…(Zakrzewski 1975, Carpita and Tarmann 1982, Terry et al 1982 and to inhibit the elongation of currentyear Pinus sylvestris L. shoots when applied around the circumference of the subjacent previous-year (1-year-old) shoot (Sundberg and Little 1990). In addition, both a positive relationship and no relationship have been reported between the concentration of endogenous IAA and the rate of shoot elongation in woody species (Dunberg 1976, Wood 1983, Sandberg and Ericsson 1987, Buta et al 1989, Rodríguez et al 1991, Browning et al 1992, Yang et al 1992, Rinne et al 1993.…”
Section: Introductionmentioning
confidence: 99%
“…(Zakrzewski 1975, Carpita and Tarmann 1982, Terry et al 1982 and to inhibit the elongation of currentyear Pinus sylvestris L. shoots when applied around the circumference of the subjacent previous-year (1-year-old) shoot (Sundberg and Little 1990). In addition, both a positive relationship and no relationship have been reported between the concentration of endogenous IAA and the rate of shoot elongation in woody species (Dunberg 1976, Wood 1983, Sandberg and Ericsson 1987, Buta et al 1989, Rodríguez et al 1991, Browning et al 1992, Yang et al 1992, Rinne et al 1993.…”
Section: Introductionmentioning
confidence: 99%
“…Grochowska et al (1984) showed that the auxin level in leaves and buds of tall apple trees was higher than in dwarf ones. On the other hand, in the experiment with these plants, the gas chromatography-mass spectrometry (GC-MS) assay showed that the IAA level was higher in the buds and lower in the leaves of dwarf plants than in tall plants (Buta et al, 1989). No difference was revealed between auxin contents in the apical part of scions of normal and column-shaped apple species during the period of intense growth of new scions (Watanabe et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Using the Avena curvature test for auxin measurement, Grochowska et al (1984) showed that IAA levels in leaves and buds of sib crossings of the apple cultivars Goldspur and Redspur were higher in vigorous than in dwarf trees. Buta et al (1989) used a GC-SIM-MS method for auxin measurement in the same apple population and showed that IAA levels in buds were higher in dwarf than in vigorous trees, whereas in leaves the relationship was just the opposite. In contrast, Wlosek-Stangret et al (2000) did not find any significant differences in free or bound IAA levels in leaves of 'Jonagold' apple trees grafted on various rootstocks.…”
Section: Introductionmentioning
confidence: 97%